Perbandingan Penetapan Harga Pokok Produksi Menggunakan Metode Full Costing Dengan Penetapan Harga Oleh UMKM - Obby Anggara; Puji Isyanto; Neni Sumarni (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
Production costs are very important to increase business competition by providing quality products at competitive prices. However, many UMKM directly calculate production costs, causing uncertain cost estimates. This research was conducted at Pak Nanang's tofu UMKM which aims to determine the correlation and comparison of the estimated production costs by UMKM using the full costing technique. The research method used is descriptive qualitative. Important information is obtained from meetings with business actors and data recording in a straightforward manner as well as from relevant previous research references related to the title. The results showed that the calculation using the full costing technique showed a higher value compared to the calculation by Pak Nanang's tofu UMKM. The results obtained for the UMKM strategy amounted to Rp. 218.75 per piece of tofu while Rp. 280.53 for the full costing technique and the difference obtained was Rp. 61,78. This finding shows that the full costing strategy provides accurate estimates in determining production costs which can help UMKM make more appropriate choices to run their business more productively.